Histopathological Change of White Mouse Ovary as a Result of Ethylene Glycol Intoxication - Budiman, Hamdani; Akmal, Muslim; N. Siregar, Tongku (Jurnal Kedokteran Hewan, 2008)
This research was aimed to know histopathology change of white mouse ovary as result of EG intoxication. Eight white mice randomly divided into three treatment groups and one control group. Treatment of P1 group was given 10 ml EG/L drinking water, P2 was given 20 ml EG/L drinking water, and P3 was given 30 ml EG/L drinking water for two weeks. Control group was given aquadest. Then, white mice were euthanized and ovaries sample were taken for histology observation. The result for treatment groups (P1 and P2) had shown ovary hyperemic (congest). But, the change is worst in P2 rather than P1. Changes in P3 treatment group had shown ovary hyperemic (congest) and leukocyte infiltration in follicular antrum and follicular necrosis causing lost of ovum cell (cariolysis). Poisoned of EG in white mouse can cause inflammation and necrosis of ovary follicle thus the formed of ovum cell was failed (ovogenesis).